Avaliação da dureza superficial de resinas compostas antes e após o polimento em diferentes tempos - Chinelatti, Michelle Alexandra (2006)
PURPOSE: The aim of this study was to evaluate the surface hardness of six composite resins: Revolution, Natural Flow, Fill Magic Flow, Flow-it! (flowables), Silux Plus (microfilled) and Z100 (minifilled) before and after polishing at different times. MATERIALS AND METHODS: For this purpose, 240 specimens (5mm diameter, 1.4mm high) were prepared. Vickers hardness was determined before and after polishing at different times: immediately, 24h, 7 and 21 days after preparation of the samples. Statistical analysis was performed by ANOVA and Tukey test. RESULTS: There was no difference in the hardness of flowable resins, which had lower hardness than the minifilled resin. The minifilled resin showed the highest surface hardness as compared to the other materials (p